2003
DOI: 10.1016/s1097-2765(03)00116-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a Single Pore Subcomplex Results in Vertebrate Nuclei Devoid of Nuclear Pores

Abstract: The vertebrate nuclear pore complex, 30 times the size of a ribosome, assembles from a library of soluble subunits and two membrane proteins. Using immunodepletion of Xenopus nuclear reconstitution extracts, it has previously been possible to assemble nuclei lacking pore subunits tied to protein import, export, or mRNA export. However, these altered pores all still possessed the bulk of pore structure. Here, we immunodeplete a single subunit, the Nup107-160 complex, using antibodies to Nup85 and Nup133, two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
297
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(310 citation statements)
references
References 65 publications
13
297
0
Order By: Relevance
“…Such a study previously revealed that partial depletion of Nup133, Nup107, or Nup85 leads to the decreased localization of several nucleoporins at the nuclear envelope (Boehmer et al, 2003;Harel et al, 2003;Walther et al, 2003a). We could further correlate this decreased labeling to an overall decrease of NPC number in the Nup133 or Nup107-depleted cells (Walther et al, 2003a).…”
Section: Rna Interference Of Seh1 Induces Phenotypes Similar To Nup13mentioning
confidence: 52%
See 4 more Smart Citations
“…Such a study previously revealed that partial depletion of Nup133, Nup107, or Nup85 leads to the decreased localization of several nucleoporins at the nuclear envelope (Boehmer et al, 2003;Harel et al, 2003;Walther et al, 2003a). We could further correlate this decreased labeling to an overall decrease of NPC number in the Nup133 or Nup107-depleted cells (Walther et al, 2003a).…”
Section: Rna Interference Of Seh1 Induces Phenotypes Similar To Nup13mentioning
confidence: 52%
“…So far, three constituents of the Nup107-160 complex, Nup133, Nup107, and Nup85, have been localized to kinetochores in mitosis (Belgareh et al, 2001;Harel et al, 2003). Because those results suggested that the entire Nup107-160 complex might be targeted to kinetochores in mitosis, we analyzed the localization of GFP-tagged constituents of this complex in mitotic HeLa cells.…”
Section: Gfp-tagging Reveals the Association Of Nup160 Nup37 Nup43mentioning
confidence: 99%
See 3 more Smart Citations